Clinical and morphological characteristics of neuroendocrine tumors: clinical experience - G. A. Raskin; A. K. Ivanova; R. V. Orlova (Успехи молекулярной онкологии, 2017)
Currently, treatment and diagnostics of neuroendocrine tumors are associated with a number of problems, including absence of a registry for these diseases. The article considers the main approaches and problems of immunohistochemical diagnostics of neuroendocrine tumors.